Service Value Activities by Nurse Practitioners in Ambulatory Specialty Care. (May 2020) - Winter, Shira G.; Duderstadt, Karen; Chan, Garrett K.; Spetz, Joanne; Stephan, Linda M.; Matsuda, Erin; Chapman, Susan A.
The increase in nurse practitioners (NPs) in ambulatory medical and surgical specialty settings has prompted inquiry into their role and contribution to patient care. We explored the role and contribution of NPs in ambulatory specialty care through their activities outside of direct care and billable visits (referred to as service value activities), and how NPs perceive these activities enhance quality and efficiency of care, for both patients and the health care institution. This qualitative thematic analysis examined interviews from 16 NPs at a large academic medical center about their role and contribution to patient care quality and departmental efficiency beyond billable visits. Five categories of NP contribution were identified: promoting patient care continuity, promoting departmental continuity, promoting institutional historical and insider knowledge, addressing time-sensitive issues, and participating in leadership and quality improvement activities. As the role of NPs in specialty care grows and health care systems emphasize quality of care, it is appropriate to explore the quality- and efficiency-enhancing activities NPs perform in specialty care beyond direct patient care.